Hubungan Persepsi Dengan Motivasi Siswa Sekolah Menengah Kejuruan Dalam Konseling Perorangan - Diastuti, Diastuti; Rangka, Itsar Bolo; Prasetyaningtyas, Wahyu Eka; Renata, Dian (JURKAM: Jurnal Konseling Andi Matappa, 2017)
This study aimed to perform relationship between students perceptions on counselling practice with motivational student’s in to individual counselling process. Data collection was conducted against 288 students in Al Hidayah 1 Vocational School - Jakarta. Data analysis used the correlation coefficient test Gamma and Somers'D. The research findings showed coefficient Gamma and Somers'D test reached 0496 with Zhitung > Ztable or 6,523 > 1.96. It means there is a significant relationship and positive direction between the perceptions of students towards counselling and motivation of students followed individual counselling service